The low-carbon influencing mechanism of spatial characteristic parameters in China's residential communities. Issue 1 (2nd January 2021) - Wei, Xuan; Quan, Tang
ABSTRACT: This paper takes the spatial characteristics of residential communities in China as a case study, focusing on three aspects: (1) scale-like spatial parameters, including density and land-mass scale; (2) spatial parameters of facility space layout, including spatial distribution of public service facilities, and coverage, density of facilities, layout and coverage of road transport facilities, site density and proximity, etc.; and (3) spatial parameters of mixed classes mainly in reference to the degree of functional mix of land around the community. The study used empirical research, spatial characteristics of quantitative statistical parameters, correlation analysis, and other methods, including examination of previous case studies of residential communities. Based on the case study of three Chinese residential communities, spatial parameters such as density, plot size, facility layout and coverage, facility density and mixing degree were investigated and statistically calculated. The study revealed that the spatial features of urban residential communities can influence energy use and carbon dioxide emission in cities by affecting the travel behaviors of residents and changing the land utilization type and spatial structures of city blocks. Optimizing the layout of community space is an important way to build a low-carbon community.